A systematic review of the efficacy and safety of Rosa damascena Mill. with an overview on its phytopharmacological properties. (October 2017) - Nayebi, Neda; Khalili, Nahid; Kamalinejad, Mohammad; Emtiazy, Majid
Abstract: Rosa damascena Mill. is one of the most famous ornamental plants cultivated all over the world mostly for perfumery industries. Traditionally it has been used as an astringent, analgesic, cardiac and intestinal tonic.The paucity ofauthoritative monographs urged usto summarize its clinical effectiveness and safety with acomprehensive review of the literature. "PUBMED", "SCOPUS", "WEBOF SCIENCE" were searched up to April 30, 2017 with search terms:(" Rosa damascena " OR "Damask Rose"). All human studies with any mono-preparation were included. In vitro and animal studies from "PUBMED"were also reviewed and outlined. Of "1000" identified publications, twelveeligibleclinical trials were retrieved. Antimicrobial, anti-inflammatory, antioxidant, anticancer, protective neuronal, cardiac, gastrointestinal and hepatic effectsin 30 in vitro and 21 animal studies were also shown. there are promising evidences for the effectiveness and safety of Rosa damascena Mill in pain relief, but confirmatory studies withstandardized products is suggested.